Mechanistic insights into cisplatin-induced ototoxicity: the central role of transient receptor potential channels - Yu, Man; Li, Juanjuan; Zeng, Xianhai (Frontiers in Molecular Biosciences, 2025)
This review systematically elucidates the molecular mechanisms underlying cisplatin-induced ototoxicity, with a particular focus on the pivotal role played by TRP channels. First, the article outlines the uptake and efflux pathways of cisplatin within cochlear hair cells, followed by a detailed analysis of the core mechanisms by which cisplatin damages these cells. It emphasizes the structural and functional characteristics of TRP channels and their action mechanisms in cisplatin ototoxicity, elucidating the channels' high selectivity for calcium ions and their central role in driving ototoxicity. Additionally, the review explores the roles of other TRP family members in regulating hair cells. Finally, based on an analysis of the limitations of existing otoprotective strategies, the review proposes future precision prevention and treatment strategies targeting TRP channels. These include novel nanodelivery technologies and multi-pathway combined interventions, providing a new theoretical foundation and translational direction for protecting against cisplatin ototoxicity.